2012 American Control Conference (ACC) 2012
DOI: 10.1109/acc.2012.6315360
|View full text |Cite
|
Sign up to set email alerts
|

A Smoothed GMS friction model suited for gradient-based friction state estimation

Abstract: Abstract-The multi-state Generalized Maxwell-Slip (GMS) friction model is known to describe all essential friction characteristics in presliding and sliding motion. It is also known that due to its switching state conditions between presliding and sliding, gradient-based parameter and state estimation methods cannot be implemented efficiently. Efficient on-line state and parameter estimation is essential for model-based friction compensation in order to track changes of friction characteristics in time and spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In [28], a modified Maxwell-slip (MMS) model is developed for identifying the asymmetric hysteresis of a class of piezo-actuators. The MMS model involves the typical switching structure of the Maxwell-slip form that makes the online parameter identification difficult, as pointed out in [29]. A total of 42 parameters are involved in the general MMS friction model in [28], whereas 40 parameters characterize the Prandt-Ishlinskii model of a PAM in [17].…”
Section: Identification Results and Discussionmentioning
confidence: 99%
“…In [28], a modified Maxwell-slip (MMS) model is developed for identifying the asymmetric hysteresis of a class of piezo-actuators. The MMS model involves the typical switching structure of the Maxwell-slip form that makes the online parameter identification difficult, as pointed out in [29]. A total of 42 parameters are involved in the general MMS friction model in [28], whereas 40 parameters characterize the Prandt-Ishlinskii model of a PAM in [17].…”
Section: Identification Results and Discussionmentioning
confidence: 99%
“…11 In addition to the above two famous models, the generalized Maxwell-slip (GMS) model was developed to predict the friction behavior in presliding regime for control purposes. 12 Over the past few years, due to the ability to approximate arbitrary nonlinear systems, neural network has been widely explored and attempted to model the nonlinear friction. A comprehensive literature review on this subject can be found in Bai and Pu 13 The Elman neural network (ENN), 14 which possesses dynamic characteristics, is employed to model the nonlinear friction of hydraulic cylinder in this work.…”
Section: Introductionmentioning
confidence: 99%
“…The LuGre model describes the asperities between two contact surfaces by elastic bristles, and true nature of dynamic friction is considered as the result of the average deflection of these bristles. In advance of the LuGre model, the Leuven model [12,13], and GMS model, authors of [14,15,19] modeled the hysteresis behavior of the dynamic friction within presliding regime. Two-state dynamic friction model [16] was also proved to be capable of capturing the hysteresis behavior.…”
Section: Introductionmentioning
confidence: 99%